Interactive effects of contamination and trematode infection in cockles biochemical performance. (December 2018) - Magalhães, Luísa; de Montaudouin, Xavier; Figueira, Etelvina; Freitas, Rosa
Abstract: Anthropogenic activities, especially those involving substances that pollute the environment can interfere with bivalve populations, as well as parasitism, a fundamental ecological interaction often neglected. In marine environments, organisms are concomitantly exposed to pollutants and parasites, a combination with synergistic, antagonistic or additive effects representing a potential threat to aquatic communities sustainability. In the present study, Cerastoderma edule (the edible cockle)– Himasthla elongata (trematode) was used as host–parasite model. Cockles are worldwide recognized as good sentinel and bioindicator species and can be infected by several trematodes, the most abundant macroparasites in coastal waters. Tested hypotheses were: 1) cockles exposed to increasing parasite pressure will present greater stress response; 2) cockles exposure to arsenic (single concentration test: 5.2 μg L −1 ) will change parasite infection success and cockles stress response to infection. Arsenic was used for being one of the most common pollutants in the world and stress response assessed using biochemical markers of glycogen content, metabolism, antioxidant activity and cellular damage. Results showed that intensity of parasite pressure was positively correlated to biochemical response, mainly represented by higher metabolic requirements. Contamination did not affect parasite infection success. Compared to arsenic, trematode infection alone exerted a stronger impact: higher glycogen storage, metabolism and cellular damage and antioxidant activity inhibition. In interaction, parasitism and arsenic reduced hosts metabolism and cellular damage. Therefore, to a certain extent and in a contamination scenario, cockles may benefit from trematode infection, working as a protection for the pollutant accumulation in the organisms, reducing overall ROS production, which can consequently led to less toxic effects. These findings highlighted the deleterious effects of trematode infection in their hosts and showed the importance of including parasitology in ecotoxicological studies. Graphical abstract: Image 1 Highlights: In the environment organisms are concomitantly exposed to pollutants and parasites. Parasite pressure intensity positively correlated to higher metabolic requirements. Arsenic contamination (5.2 μg L −1 ) did not affect parasite infection success. Trematode infection exerted a stronger impact on cockles than arsenic. Trematodes and arsenic interaction exerted antagonistic effects on cockles. Abstract : Arsenic contamination did not affect parasite burden but the interaction parasitism and arsenic reduced hosts metabolism and cellular damage.